IMPROVING ENGLISH SPEAKING ABILITY THROUGH HYPNOCATIVE SPEECH METHOD - Ninin Herlina (University of Kuningan, 2018)
The objective of this research is to identify the improvement of students’ English speaking ability through hypnocative speech. The research was conducted at Mantika Language Center. This action research was carried out in two cycles in which each cycle consists of four phases of planning, action, observation, and reflection. Here, the researcher guided the instructor as students’ collaborators in implementing hypnocative speech method to improve students’ English speaking ability. The data collection techniques used were observation, questionnaire, test, teacher's diary, observer’s daily journal, interviews, and audiotape recordings. The data consist of collected accent, grammar, fluency, vocabulary and comprehension. The data have been collected through a critical comparative analysis technique by combining and simultaneously comparing the result of the first cycle until the last cycle. As result, it was found that implementing hypnocative speech in the teaching and learning process can improve students’attitudes and the outcome of their speaking ability. Here, the students can communicate fluently, do not feel afraid, and have more courage to speak the language communicatively, harmoniously, and correctly. Precisely, the implementation of hypnocative speech method can increase students’ speaking ability, at least 30.31.Keywords: action research; speaking ability; hypnocative speech.